2001
DOI: 10.1021/jp004116t
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Amino Acid Precursors in the Interstellar Medium. A DFT Study of Some Gas-Phase Reactions Starting with Methylenimine

Abstract: To evaluate feasibility of the formation of amino acid precursors in dense interstellar clouds from methylenimine, HCN, ‚CN radical, water, and ‚OH radical, stationary points for four gas-phase reactions have been computed at the B3LYP/6-311++G(d,p) level of theory. All the reactions are exothermic. For the reaction HNdCH 2 + HsCtN f H 2 NsCH 2 sCtN, three high-energy transition states have been found (energies of ca. 23-33 kcal mol -1 relative to the reactant level) which do not allow this reaction to occur a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 73 publications
1
39
0
Order By: Relevance
“…Several proposals of different neutral-neutral reactions have been made (Hoyle 1976;Maeda & Ohno 2004a,b, 2006Basiuk & Kobayashi 2004;Andreazza et al 2006). In some cases theoretical studies have been carried out (Basiuk & Bogillo 2000;Basiuk 2001) that conclude that these processes are not feasible under interstellar conditions. Ion-molecule reactions are more promising, since in many cases they are more likely to proceed without involving energy barriers.…”
Section: Introductionmentioning
confidence: 99%
“…Several proposals of different neutral-neutral reactions have been made (Hoyle 1976;Maeda & Ohno 2004a,b, 2006Basiuk & Kobayashi 2004;Andreazza et al 2006). In some cases theoretical studies have been carried out (Basiuk & Bogillo 2000;Basiuk 2001) that conclude that these processes are not feasible under interstellar conditions. Ion-molecule reactions are more promising, since in many cases they are more likely to proceed without involving energy barriers.…”
Section: Introductionmentioning
confidence: 99%
“…Hoyle & Wickramasinghe (1976) suggested the formation of glycine from the reaction of methanimine (HNCH 2 ) and formic acid (HCOOH) since these compounds had been observed in dense molecular clouds of comparable abundance. In this context, Basiuk & Bogillo (2000), Basiuk (2001), and Basiuk & Kobayashi (2002) carried out a theoretical study of amino-acid-precursor formation in the interstellar medium considering different pathways that include the participation of methanimine and methanimine-related cations, HNCH + and H 2 NCH 2 + . Their studies demonstrated that although the reactions considered are exothermic they are not feasible under the interstellar conditions because of the high energy transition states and the possibility of competitive formation of side products.…”
Section: Introductionmentioning
confidence: 99%
“…HNC, the isomer of HCN, was also included as a direct reactant since it is more reactive though less stable [18]. Formamide is dissymmetric and may tautomerize to formamidic acid, which has been also investigated as a catalyst in the addition (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%